Analisis Konsep Feminisme Psikoanalisis dalam Konteks Kekerasan Seksual - Muhammad Imam Alfikri; Ignatius Aji Dwiatmaja (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Sexual violence is one of the problems that plague many women in today's society. In an effort to understand the root causes and impacts of sexual violence, psychoanalytic feminism has emerged as a relevant theoretical framework. This research uses a qualitative approach with theoretical analysis. Through a review of literature relating to psychoanalytic feminism, sexual violence, and patriarchy, this journal reveals the complex relationship between the three concepts. Psychoanalytic feminism addresses how patriarchal structures affect women's lives and reinforce sexual violence as a tool of gender domination. The analysis in this journal highlights the importance of understanding the social and psychological context in understanding and addressing sexual violence. Psychoanalytic feminism emphasizes the important role of gender identity, social construction, and trauma in analyzing sexual violence. Through this research, it is hoped that a deeper understanding of the complexities of sexual violence as a direct result of patriarchal structures can be achieved. Through this analysis, this journal provides a deeper understanding of the complexity of sexual violence and its impact on victims. The practical impact of this research is to raise awareness about sexual violence in the community, as well as to encourage a gender-based approach in the prevention and handling of this problem.